A Study of Various Web Page Recommendation Algorithms (International Journal of Engineering and Computer Science, 2015)
Web-page recommendation plays an important role in intelligent Web systems. Recommender system apply various techniques and prediction algorithm to predict user interest on information, items and services from the tremendous amount of available data on the internet. The paper studies various algorithm in weka and the metrices used to evaluate algorithm performance. The basic algorithm or predictive model we use are – page rank, Rule mining collaborative filtering, Context matching simple linear regression, k-nearest neighbours(kNN), naives bayes, support vector machine.